Charge exchange recombination spectroscopy of Wq+ (q = 61–66) for application to ITER neutral hydrogen beam diagnostics. (30th September 2021) - Dipti; Schultz, D R; Ralchenko, Yu
Abstract: In this paper, we present a detailed theoretical analysis of charge exchange recombination spectroscopy based on interactions of the planned ITER neutral beams (diagnostic beam of 100 keV u −1 and heating beam of ≍1 MeV u −1 ) with highly-charged ions of tungsten. The results of the present spectral synthesis are based on the new set of nl -resolved charge exchange (CX) cross sections for recombination of the W q + ions ( q = 61–66) with atomic hydrogen calculated using the classical trajectory Monte Carlo method. A large-scale collisional-radiative model describing the population kinetics of the high- n atomic states of Si-like through O-like W ions has been developed using the NOMAD code for typical conditions of the ITER core plasma, and the resulting spectra have been generated for wavelengths in the x-ray to visible range (0.1–1000 nm). A detailed analysis of the plasma emission predicts a significant effect of CX recombination on the W line intensity ratios that can be used for more advanced diagnostics of the ITER plasma.